Canadian Clinical Practice Guidelines for Rosacea. Issue 5 (September 2016) - Asai, Yuka; Tan, Jerry; Baibergenova, Akerke; Barankin, Benjamin; Cochrane, Chris L.; Humphrey, Shannon; Lynde, Charles W.; Marcoux, Danielle; Poulin, Yves; Rivers, Jason K.; Sapijaszko, Mariusz; Sibbald, R. Gary; et al.
Rosacea is a chronic facial inflammatory dermatosis characterized by background facial erythema and flushing and may be accompanied by inflammatory papules and pustules, cutaneous fibrosis and hyperplasia known as phyma, and ocular involvement. These features can have adverse impact on quality of life, and ocular involvement can lead to visual dysfunction. The past decade has witnessed increased research into pathogenic pathways involved in rosacea and the introduction of novel treatment innovations. The objective of these guidelines is to offer evidence-based recommendations to assist Canadian health care providers in the diagnosis and management of rosacea. These guidelines were developed by an expert panel of Canadian dermatologists taking into consideration the balance of desirable and undesirable outcomes, the quality of supporting evidence, the values and preferences of patients, and the costs of treatment. The 2015 Cochrane review "Interventions in Rosacea" was used as a source of clinical trial evidence on which to base the recommendations.